Extrusion Foaming of a Preceramic Silicone Resin with a Variety of Profiles and Morphologies - Wolff, Friedrich; Ceron Nicolat, Bruno; Fey, Tobias; Greil, Peter; Münstedt, Helmut (Advanced Engineering Materials, 2012)
Preceramic foams with a variety of profiles and morphologies were fabricated by a continuous foam extrusion process based on a single-screw extruder. A methyl silicone resin was used as the preceramic polymer and carbon dioxide as the foaming agent. Variations of the foam morphology were achieved by changing the key process parameters carbon dioxide content, foaming pressure, and foaming temperature. Samples of different porosities, cell densities, pore sizes, and pore size gradients were obtained. From these results, conditions for the fabrication of particular foam structures can be derived. Various foam profiles as rods, tapes, and tubes were extruded and pyrolysed into ceramic foams.

Graded Cellular Ceramics from Continuous Foam Extrusion - Ceron Nicolat, Bruno; Wolff, Friedrich; Dakkouri, Andrea S.; Fey, Tobias; Münstedt, Helmut; Greil, Peter (Advanced Engineering Materials, 2012)
Cylindrical SiOC foam filaments with a radial gradient in pore cell size were processed by continuous extrusion foaming of a methyl polysilsesquioxane. Upon leaving the extrusion nozzle foaming was initiated by pressure release which caused precipitation of supersaturated carbon dioxide from the polymer filament. Rapid cooling of the thin filaments generates a radial gradient of melt viscosity which gives rise for formation of closed cell morphology of isotropic pore cells in the core (diameter?<!–?200?mu m) and non-isotropic pore cells near the sur-face (shell; <20?mu m). After pyrolysis at temperatures ranging from 800 to 1400?degrees C the stabilized polymer gradient foams were converted into closed cell SiOC ceramic gradient foams. XRD reveals the SiOC residue to be amorphous up to 1200?degrees C whereas crystallization of beta-SiC was observed at 1400?degrees C. A superior compressive strength of 9?MPa and a Young's modulus of 7?GPa at a relative density of 0.18 were measured at an optimum pyrolysis temperature of 1000?degrees C.–>
Keywords: carbon dioxide foaming; graded porosity; polymer derived cellular ceramics

Using Supercritical Carbon Dioxide for Physical Foaming of Advanced Polymer Materials - Wolff, Friederich; Zirkel, Larissa; Sarah, Betzold; Jakob, Matthias; Verena, Maier; Nachtrab, Frank; Ceron Nicolat, Bruno; Fey, Tobias; Münstädt, Helmut (International Polymer Processing, 2011)
Foams from high performance polymers find more and more interest. The processes to generate them can be difficult, however. It is shown how physical foaming with CO2 can be used as a first step to assess the potentials of such materials. For investigations of such kind an autoclave on a laboratory scale which allows pressure variations up to 300 bars and temperatures up to 300 degrees C was set up. The samples are saturated with supercritical carbon dioxide (s.c. CO2) which acts as a foaming agent. Depending on the process and material parameters different foam characteristics and cell morphologies were obtained and characterised. The potential of this method is demonstrated for two different classes of advanced polymer materials, thermoplastic fluoropolymers (PEP), and a silicone resin. In the case of the fluoropolymer, previously prepared films were foamed and the effects of various process parameters on the foam characteristics were investigated. Besides the general potential of foams from fluoropolymers, they are candidates for polymeric piezoelectric materials with a relatively high temperature stability. Silicone polymers possess some properties superior to common organic polymers. First results on the foaming behaviour of a silicone resin are presented.